Measuring Efficiency of Hospitals by DEA: An Empirical Evidence from Pakistan - Syed Aziz Rasool; Abdul Saboor; Muhammad Raashid (International Journal of Public Health Science (IJPHS), 2014)
ABSTRACT There has been increasing focus on efficiency measurement in health sector around the world. This empirical study aims at measuring efficiency level of non-profit private organization by using Data Envelopment Analysis (DEA) in the health sector of Pakistan. DEA is non-parametric linear programming based approach for homogeneous decision making units. Layton Rehmatullah Benevolent Trust (non-profit private organization) will be subject matter for investigational analysis constituting over 16 sub-units spreading across the country. Secondary data of number of patient beds, specialists and nurses in all the 16 branches of LRBT hospitals will be used applying quantitative specification tool, both scale and technical efficiency levels in an environment where multiple of inputs and outputs are in place, will be used for final evaluation. The outcomes so expected will help policy makers to formulate effective plans and programs in order to enhance the efficiency of health measures conducted by non- profit private organizations.